On Question for the Preposition Constructions “OT” + Genitive of Nouns with the Mediate Subject Meaning in the Russian Language - Лычинская, М. С. (Kalbotyra, 1994)
The problem, analysed in this article, relates to the communicative syntax. The nominal constructions with preposition “OT” are examined as predicative units in the contracted form.